2015
DOI: 10.1371/journal.pone.0144338
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ-LAP*/LAP Expression Is Mediated by RSK/eIF4B-Dependent Signalling and Boosted by Increased Protein Stability in Models of Monocytic Differentiation

Abstract: The transcription factor C/EBPβ plays a key role in monocytic differentiation and inflammation. Its small isoform LIP is associated with proliferation at early premonocytic developmental stages and regulated via mTOR-dependent signalling. During later stages of (pre)monocytic differentiation there is a considerable increase in the large C/EBPβ isoforms LAP*/LAP which inhibit proliferation thus supporting terminal differentiation. Here, we showed in different models of monocytic differentiation that this dramat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…However, CEBPB had three protein isoforms: LAP* (38KD), LAP (35KD) and LIP (20KD) [35]. Subtype LIP that exhibits inhibitory effects could be produced by the LAP* and LAP subtypes [36]. Moreover, studies on the transcription factor Deaf-1 have shown that it exhibits an up-regulation function on the expression of 5-HT1A auto-receptor and an inhibitory effect on the 5-HT1A post-synaptic receptor expression [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, CEBPB had three protein isoforms: LAP* (38KD), LAP (35KD) and LIP (20KD) [35]. Subtype LIP that exhibits inhibitory effects could be produced by the LAP* and LAP subtypes [36]. Moreover, studies on the transcription factor Deaf-1 have shown that it exhibits an up-regulation function on the expression of 5-HT1A auto-receptor and an inhibitory effect on the 5-HT1A post-synaptic receptor expression [14].…”
Section: Discussionmentioning
confidence: 99%
“…LIP lacks the activation domain and is thus thought to be the dominant negative isoform of LAP. 36) The ratio of LAP/LIP was considered as an in-THE ROLE OF C/EBPβ IN CARDIAC FIBROSIS dicator for C/EBPβ activity. Our studies demonstrated an increase in the LAP/LIP ratio in C/EBPβ knockdown studies.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and Western Blot analysis were performed using standard protocols as described in [ 77 ]. The protein content in whole-cell extracts from K4IM cells was determined using the bicinchoninic acid assay (Pierce, Rockford, IL, USA).…”
Section: Methodsmentioning
confidence: 99%